Upaya Peningkatan keamanan Pangan pada Pelaku Usaha Pangan Segar Asal Tumbuhan (PSAT) di Kota Mataram - M. Sarjan; Aluh Nikmatullah; Hery Haryanto; Ruth Stella Thei; Amrul Jihadi (Unram Journal of Community Service, 2022)
As a result of the outbreak of the COVID-19 pandemic which was followed by the imposition of large-scale social restrictions (PSBB) in Indonesia, it has encouraged people to adopt healthier lifestyles and at the same time carry out a number of environmentally friendly activities. Therefore, it is necessary to make efforts to improve understanding and practice of cultivation as well as guarantee the quality of the food produced, among others by carrying out socialization "how to register horticultural products in urban areas to obtain a Prima3 certificate" as a guarantee that it is safe for consumption. The method used in this activity is the Action Research Method by applying the Participatory Action Program approach from the participants through discussions, and group work in all activities. The results of the activity show that one of the efforts to improve food safety for business actors of Fresh Plant-Origin Food (PSAT) is by registering for food safety certification. Based on survey results from 6 survey locations, 5 of them are still active, namely Japri Farm, UD Rohana and KWT Bunga Matahari, UD Sari Melanting, and UD Sumber Sari. While 1 other location is not active, namely KP. Petemon Asri. There are several business actors in the City of Mataram who have not extended the registration of the commodities they produce. These actors include the Bijak Sari Poktan, the Farmer Family Farmers Group, Japri and Mataram Hydroponics. The results of the demonstration plot showed that the use of liquid organic fertilizer was able to grow lettuce plants well. The best use of vegetable pesticides is demonstrated by plant-based pesticides extracted from papaya leaves. Botanical pesticides are pesticides whose active ingredients come from plants or herbs and other organic materials that can control pest attacks on lettuce plants, both as repellents, antifedans, attractants.